Analisis Sektor Unggulan Sebagai Daya Saing Dalam Pembangunan Wilayah Kabupaten - Ahmad Amri Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The basic sectors or leading sectors of a region need to be explored optimally to increase economic competitiveness. Measuring competitiveness can be done by identifying basic sectors, Shift-Share analysis and also Klassen typology analysis. The aim of this research is to analyze the leading sectors in Purbalingga Regency based on Gross Regional Domestic Product (GRDP) data in order to obtain basic sectors, classification of economic growth and changes and shifts in the economic structure. This research is a quantitative research using Location Quotient (LQ) analysis tools, Shift-Share analysis and Klassen Typology analysis. The result is that based on the LQ analysis, there are three superior out of fourteen superior GRDP sectors, namely the Agriculture, Forestry and Fisheries sectors, the Mining and Excavation sector and the Water Supply, Waste Management, Waste and Recycling sectors. Furthermore, the five sectors that are included in the advanced and rapidly growing sector include the Transportation and Warehousing sector, the Government Administration, Defense and Mandatory Social Security sectors, the Mining and Quarrying sector, the Education Services sector and the Agriculture, Forestry and Fisheries sectors. The results of the Shift-Share analysis show that there are six sectors that fall into the basic category which is superior, namely the Construction sector, the Electricity and Gas Procurement sector, the Transportation and Warehousing sector, the Accommodation and Food and Drink Provision sector, the Health Services and Social Activities sector and the Other Services sector